Peran Guru Tahfidz Al-Qur’an dalam Meningkatkan Kualitas Hafalan Al-Qur’an pada Siswa di SMP-T Darul ‘Amal - Siti Qomariyah; Tedi Tedi; Toha Suryana; Emat Muslihat (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze the role of the Tahfidzul Qur’an teacher in improving the quality of Qur’an memorization among students at SMP-T Darul ‘Amal. The background of this research highlights the importance of tahfidz education as an integral part of Islamic character development, which emphasizes not only the quantity of memorization but also the quality of internalizing Qur’anic values in students’ daily lives. The objective is to examine how tahfidz teachers carry out their roles in the Qur’an learning process and how this impacts students’ memorization abilities and religious attitudes.  The research employs a qualitative approach using a case study design, with data collected through direct observation, in-depth interviews, and documentation of teaching activities. The findings reveal that the role of tahfidz teachers is highly significant in guiding students through methods such as talaqqi (direct transmission), structured muraja’ah (review), discipline development, and spiritual motivation. The learning environment created by these teachers also fosters a conducive and religious atmosphere. The study concludes that the success of improving Qur’an memorization quality greatly depends on the teacher’s competence, emotional connection with students, and the teaching strategies applied. These elements collectively contribute to shaping a generation that loves the Qur’an, upholds strong morals, and demonstrates a sense of responsibility.